Analysing the types of evidence used by Australian federal parliamentary committees. Issue 2 (3rd August 2021) - Ray, Andrew; Young, Arabella; Grant, Will J.
Abstract: Policy makers globally often claim to use evidence when making policy decisions, but few studies have documented and evaluated the sources of evidence they rely on. This poses challenges to researchers and decision makers alike, as they struggle to assess the impact of research on policy. This study analysed citations in Australian federal parliamentary committee reports to better understand the role that academic sources play in shaping policy. Results show that academic sources are rarely cited by federal parliamentary committees, and of those that are cited, most are academic inquiry submissions or oral evidence, with very few citations of peer‐reviewed research. This finding points towards a need for academics seeking policy impact to engage more pro‐actively with government inquiry submission processes. To incentivise this approach, we suggest that changes be made to the way that academic impact is measured within the university sector in order to avoid disincentivising researchers from making submissions to parliamentary inquiries. Abstract : Our study draws on previous literature and develops a method to assess the use of academic evidence in federal parliamentary committee reports. Our results demonstrate that little peer‐reviewed evidence is cited, and that for researchers to 'impact' the committee process they need to engage directly with government through writing submissions.